2016
DOI: 10.1080/13510002.2016.1239866
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress biomarkers in pediatric sepsis: a prospective observational pilot study

Abstract: Objectives: Oxidative stress is known to participate in the progression of sepsis. Definite data regarding the behavior of oxidative stress biomarkers in pediatric sepsis is still lacking. This study hypothesized that oxidative stress occurs in pediatric sepsis and that the magnitude of the redox derangement is associated with worse clinical progression. Methods: Forty-two previously healthy pediatric patients with sepsis and a group of control subjects were included. Oxidative stress and inflammatory activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Sepsis, which has many complications, such as MODS, hypotension, and pathoglycemia, exhibits a high mortality rate stemming from a systemic infection 1 3 . Sepsis is characterized by an uncontrolled inflammatory response and oxidative stress 4 , 5 . Inflammatory mediators, including IL-1RN, IL-6, and TNF-α, and effector cells, including neutrophils and macrophages are important causes in the pathogenesis of sepsis 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis, which has many complications, such as MODS, hypotension, and pathoglycemia, exhibits a high mortality rate stemming from a systemic infection 1 3 . Sepsis is characterized by an uncontrolled inflammatory response and oxidative stress 4 , 5 . Inflammatory mediators, including IL-1RN, IL-6, and TNF-α, and effector cells, including neutrophils and macrophages are important causes in the pathogenesis of sepsis 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that the oxidant/antioxidant balance played a prominent role in the pathogenesis of sepsis and LPS administration led to oxidative stress injury [5]. In the present study, we identified the antioxidant effects of exercise.…”
Section: Discussionmentioning
confidence: 73%
“…Sepsis, which has many complications, such as MODS, hypotension, and hypoglycemia, exhibits a high mortality rate stemming from a systemic infection that involves alterations in inflammatory parameters and oxidative status [1][2][3]. The pathogenesis of sepsis is complex and inflammation and oxidative stress play critical roles in the pathogenesis of sepsis [4,5]. Sepsis is characterized by an uncontrolled inflammatory response involving inflammatory mediators, including IL-1RN, IL-6, IL-10, and TNF-α, and effector cells, among which neutrophils play a key role [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress has been implicated in the pathogenesis of sepsis [36, 37]. Taurine can enhance the ability of the antioxidant defence system by protecting antioxidant enzymes [38].…”
Section: Discussionmentioning
confidence: 99%